Gastrointestinal modifications and bioavailability of brown seaweed phlorotannins and effects on inflammatory markers. Issue 7 (16th February 2016) - Corona, Giulia; Ji, Yang; Anegboonlap, Prapaporn; Hotchkiss, Sarah; Gill, Chris; Yaqoob, Parveen; Spencer, Jeremy P. E.; Rowland, Ian
Abstract: Brown seaweeds such as Ascophyllum nodosum are a rich source of phlorotannins (oligomers and polymers of phloroglucinol units), a class of polyphenols that are unique to Phaeophyceae. At present, there is no information on the bioavailability of seaweed polyphenols and limited evidence on their bioactivity in vivo . Consequently, we investigated the gastrointestinal modifications in vitro of seaweed phlorotannins from A. nodosum and their bioavailability and effect on inflammatory markers in healthy participants. In vitro, some phlorotannin oligomers were identified after digestion and colonic fermentation. In addition, seven metabolites corresponding to in vitro -absorbed metabolites were identified. Urine and plasma samples contained a variety of metabolites attributed to both unconjugated and conjugated metabolites (glucuronides and/or sulphates). In both urine and plasma, the majority of the metabolites were found in samples collected at late time points (6–24 h), suggesting colonic metabolism of high-molecular-weight phlorotannins, with three phlorotannin oligomers (hydroxytrifuhalol A, 7-hydroxyeckol, C-O-C dimer of phloroglucinol) identified in urine samples. A significant increase of the cytokine IL-8 was also observed. Our study shows for the first time that seaweed phlorotannins are metabolised and absorbed, predominantly in the large intestine, and there is a large inter-individual variation in their metabolic profile. Three phlorotannin oligomers present in the capsule are excreted in urine. Our study is the first investigation of the metabolism and bioavailability of seaweed phlorotannins and the role of colonic biotransformation. In addition, IL-8 is a possible target for phlorotannin bioactivity.